2019
DOI: 10.3847/1538-4357/ab3e33
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Pre-flare Solar Coronal Magnetic Fields: Magnetic Flux Ropes

Abstract: Magnetic flux ropes (MFRs) are thought to be the central structure of solar eruptions, and their ideal MHD instabilities can trigger the eruption. Here we performed a study of all the MFR configurations that lead to major solar flares, either eruptive or confined, from 2011 to 2017 near the solar disk center. The coronal magnetic field is reconstructed from observed magnetograms, and based on magnetic twist distribution, we identified the MFR, which is defined as a coherent group of magnetic field lines windin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 73 publications
4
95
1
Order By: Relevance
“…According to Liu et al (2016) the spatial variations of T w can be used to locate the flux rope axis. The authors show that the axis is found as the local extremum, either peak, or a dip, in the T w map (see also Duan et al, 2019, for example this approach). This method gives thus the coordinates for the axis in the selected plane and those can be used as the seed to draw the axis.…”
Section: Flux Rope Axis and Apexmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Liu et al (2016) the spatial variations of T w can be used to locate the flux rope axis. The authors show that the axis is found as the local extremum, either peak, or a dip, in the T w map (see also Duan et al, 2019, for example this approach). This method gives thus the coordinates for the axis in the selected plane and those can be used as the seed to draw the axis.…”
Section: Flux Rope Axis and Apexmentioning
confidence: 95%
“…In this definition J is the electric current density parallel to the magnetic field and ds is the increment of the arc length along the field line. We define the flux rope to consist of the field lines that have |T w | > 1 with a constant sign within a coherent region (similar to e.g., Liu et al, 2016;Duan et al, 2019).…”
Section: Flux Rope Identificationmentioning
confidence: 99%
“…Solar eruptions are spectacular manifestation of explosive release of magnetic energy in the Sun's atmosphere, i.e., the solar corona, and therefore, unveiling the relevant magnetic field structures and their evolution holds a central position in the study of solar eruptions. Magnetic flux rope (MFR), a bundle of twisted magnetic field lines winding around a common axis with the same sign, is believed to be a fundamental structure in solar eruptions [1][2][3], especially in those which successfully produce coronal mass ejections (CMEs). By reconstruction of the cross section of ICME (i.e., CMEs that evolves into the inter-planetary space) from the in-situ data obtained by satellites passing through the ICME, it has been well established that typical ICMEs have structure of highly twisted MFR (e.g., [4,5]).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic topology is a simple arcade until the eruption onset and, once reconnection begins, it transforms to complex one having a highly twisted MFR formed during the eruption. To reveal the variation of magnetic topology, we inspected the distribution and evolution of two parameters, the magnetic squashing degree and magnetic twist number, which are commonly used for study of 3D magnetic fields and their dynamics [70,71,72,73,74,75]. The magnetic squashing degree Q quantifies the gradient of magnetic field-line mapping with respect to their footpoints, and it is helpful for searching QSLs of magnetic fields [76], which can have extremely large values of Q (e.g., ≥ 10 5 ) and are preferential sites of magnetic reconnection.…”
Section: A9 Evolution Of Magnetic Topology and Formation Of Mfrmentioning
confidence: 99%